2011
DOI: 10.3945/ajcn.110.011221
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality and the risk of cardiovascular disease: the Women’s Health Initiative (WHI)

Abstract: Overall, adherence to current nutrient guidelines (as indexed by the DMI) are associated with lower total CVD risk, and additional dietary factors (as indexed by the AHEI) were associated with a lower risk of CVD and HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 24 publications
3
94
0
2
Order By: Relevance
“…In Nordic countries, local recommendations and adherence to them might have a beneficial effect on abdominal obesity (28) and health (29)(30)(31) . In cross-sectional studies, the Healthy Eating Index (HEI), AHEI and the DASH (Dietary Approaches to Stop Hypertension) diet have been related with a lower risk of abdominal adiposity (32)(33)(34) and with a lower risk of CVD and heart failure (5,6,(35)(36)(37) . Also longitudinal studies have shown that dietary scores are related to lower incidence of overweight and obesity and weight reduction in adults (38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…In Nordic countries, local recommendations and adherence to them might have a beneficial effect on abdominal obesity (28) and health (29)(30)(31) . In cross-sectional studies, the Healthy Eating Index (HEI), AHEI and the DASH (Dietary Approaches to Stop Hypertension) diet have been related with a lower risk of abdominal adiposity (32)(33)(34) and with a lower risk of CVD and heart failure (5,6,(35)(36)(37) . Also longitudinal studies have shown that dietary scores are related to lower incidence of overweight and obesity and weight reduction in adults (38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite an already elevated risk of type 2 diabetes in this group, it is plausible that poor diet quality, as found in this study, may further increase their risk for long-term chronic disease risk including both type 2 diabetes 14,32,33 and cardiovascular disease. 34 This highlights a need to target specific dietary changes for women with previous GDM to prevent subsequent chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Overall diet can be assessed by using composite evidence-based scores that comprise multiple nutrients and food groups, such as the Alternate Healthy Eating Index (AHEI). There is strong evidence of associations between higher AHEI (which reflects better diet quality, based on current evidence) and lower risk of diabetes, CVD, and MetS (11)(12)(13)(14)(15). Some of these studies reported stronger associations with chronic disease risk with the AHEI than with other diet quality scores (12,13,15).…”
Section: Introductionmentioning
confidence: 95%